ANALISIS PENGARUH INLET TEMPERATUR SISTEM PENDINGIN BUATAN TERHADAP KENYAMANAN TERMAL KELAS UNIVERSITAS NUSA PUTRA DENGAN METODE CFD - Agung Pratama; Jihad Hari Ramdani; Kihsan Makbil; Dwi Mardika Lestari (Jurnal Permadi : Perancangan, Manufaktur, Material dan Energi, 2021)
Air circulation needed to meet comfort standards in classrooms with artificial cooling systems (Air Conditioning) to achieve thermal comfort (Thermal comport), Thermal comfort is one aspect that must be considered when designing a classroom. because at the time of learning there is an accumulation of heat and humidity of the air that will make the room uncomfortable. This research focuses on using the Simulation Computational Fluid Dynamic (CFD) method in the classrooms of Nusa Putra Sukabumi University. Simulation using Flovent 10.1 software, the simulated room is a B3D classroom on the 3rd floor of building B of Nusa Putra University which measures 10.15 m x 4.8 m x 3.25 m. The main purpose of this study is to find out the influence of inlet temperature on artificial cooling systems. Through simulation can predict efficiently and effectively setting the temperature inlet of the most optimal artificial cooling system. In the simulation conducted 5 variations, the result is the most ineffective temperature in variation 1, variation 2 and variation 3 at room temperature 16.32 °C – 20.06 °C, belongs to the category of too cold which means the room is uncomfortable. While the room with inlet temperature variation 4 and variation 5 temperature between 21.34 °C – 22.59 °C belongs to the category of comfortable cool based on the thermal comfort standard SNI 03-6572-2001.